A critical approach to human helping in information systems: Heteromation in the Brazilian correspondent banking system. Issue 3 (September 2018) - Bailey, Diane E.; Diniz, Eduardo H.; Nardi, Bonnie A.; Leonardi, Paul M.; Sholler, Dan
Highlights: We explore heteromation (the reliance on user helping for information system success) as a labor relation and as a design strategy for ICT4D projects. We take a critical approach as we examine issues of the type of labor and amount of effort such helping requires. Empathy in terms of a felt obligation to local people spurred helping in the correspondent banking system that we studied. Context was important in shaping the extent and type of helping across four banking settings. Given the rise in heteromated systems, we discuss important concerns that heteromation raises as a labor relation and as a system design strategy.